Internal communication on Social Networks in international companies : Focus on community learning & development - Petrovková, Zuzana (2019)
This thesis acknowledges the need for comprehensive qualitative collection of learnings on effective internal communication, knowledge sharing as well as L¬earning & Development approaches in international companies. The objective of the thesis is to offer applicable recommendations for the Hilti`s global L&D department on practices proven to be successful in creating organic and engaged employee behaviour across the mentioned areas. Firstly, the thesis will define key corporate knowledge sharing and communication channels, as well as current known practices. Secondly, the thesis will present the data collected in qualitative study among 12 international companies across industries, focusing on their experience with building and management of channels and platforms enabling effective communication. Collected learnings aim to present deeper user-centric understanding of platforms designed for sharing and retention of internal knowledge as well as employee development.